ANALISIS PENGARUH PDB, KURS, PERDAGANGAN, SERTA SUKU BUNGA TERHADAP PERTUMBUHAN KREDIT BANK DI INDONESIA - Luthfir Nusa Rachman; Taufiq C Dawood (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2023)
Abstract                                                   This study aims to analyze GDP, exchange rate, trade, and interest rates affect the growth of bank credit in Indonesia. This type of research uses secondary data in the form of a time series starting from 1990-2020. The data sources to be used are obtained from Bank Indonesia and the world bank. The results of this study show that GDP, trade and interest rates partially have a positive and significant effect on bank credit growth in Indonesia. Partially, the nominal exchange rate has a negative and significant effect on the growth of bank credit in Indonesia. Based on the table above, the R-squared result is 0.003559. This means that the contribution of all independent variables in explaining the dependent variable is 0.03% in the model, while the remaining 99.97% is explained by other variables outside the regression model. Keywords: Bank Credit, Exchange Rate, GDP, Interest Rate